Water balance in pediatric nephrology: construction of a Standard Operating Procedure - Priscila Pereira de Souza Gomes; Francisca Elisângela Teixeira Lima; Patrícia Rebouças Araújo; Maria Rosivy de Oliveira; Edgla Graciela Ferreira Moreira de Brito; Jéssica Lourenço Carneiro; Luana Farias Lima; Natália Parla Rodrigues Batalha Andrade
ABSTRACT Objective: To construct a Standard Operating Procedure (SOP) about the water balance, to be used by the health team in the care of children hospitalized in a pediatric nephrology unit. Method: The study was carried out in two stages: integrative review of the literature for the development of SOP and validation by specialists. The search for literature occurred in the electronic databases PUBMED, SCOPUS, LILACS, BDENF. After the bibliographic survey the construction of the SOP was performed, which was evaluated by specialists. The analysis was performed by calculating the Content Validity Index (CVI). Results: nine studies were selected as results of the integrative review. The sample of specialists was composed of nine professionals. The study was evaluated in six items, five of which presented CVI = 1 and one obtained CVI = 0.77. Conclusion: the evaluation of specialists culminated in the validation of SOP, suggesting changes that were accepted and discussed with the literature.